Membangun Generasi Berdaya Saing: Strategi Sukses dalam Pendidikan dan Karier di SMA Islam Andalusia - Alfizi, Alfizi; Jaya , Yadi fakhruzein Terang (Apik Cahaya Ilmu, 2025)
This article is the result of a community service program aimed at equipping students of SMA Islam Andalusia with strategies to enhance their competitiveness in education and career development. The initiative focuses on building a competitive generation by providing strategies in character development, career readiness, educational innovation, and career planning. The program was implemented through a participatory seminar attended by 40 students, utilizing active discussion and reflection approaches. The results indicate an increased awareness among students of the importance of soft skills, career literacy, and social connectivity in achieving future success. This article highlights the significance of integrating character education, curriculum innovation, and strengthened career services as foundational pillars in shaping an excellent and globally competitive generation.